Nonlinear finite element analysis of RC plates and shells using the unified strength theory - Wang, Fang (2010)
The main objective and target of the present research is to develop an accurate and reliable material model for the numerical modelling of RC structures. One of the most difficult aspects in modelling RC concrete structures by the finite element method is the lack of an accurate and reliable material model for concrete. In simulating the concrete material behaviour, a new plastic-hardening model and a new plastic-damage model have been developed. The ascending potions of the new models are characterised by Kotsovos and Pavlovic's three-dimensional stress-strain relationship for concrete. What makes the present computation model peculiar is that, for the first time, Unified Twin Shear Strength (UTSS) theory is applied for FE analysis of RC plates and shells. A new strength criterion for concrete based on UTSS has been proposed by the author. It is incorporated into the new plastic-hardening and plastic-damage constitutive models for concrete.